PENGEMBANGAN MICROLEARNING VIDEO 360° PADA FENOMENA EFEK FOTOLISTRIK - Sari, Ika; Budi, Esmar; Fitri, Upik Rahma (Information Technology Education Department, 2024)
This research aims to develop a 360° microlearning video in a modern physics course on the phenomenon of the photoelectric effect. The research uses the R&D method with the ASSURE development model which consists of (1) Analyze Learners, (2) State Standars and Objectives, (3) Select Methods, Media and Materials, (4) Utilize Technology, Media, and Materials, (5) Require Learner Participation, (6) Evaluate and Revise. However, in this study, it was carried out only up to the Utilize Technology, Media, and Materials stage. Data collection was carried out using instruments in the form of a questionnaire of initial abilities, student characteristics, interviews, and documentation to students of physics education and physics study programs at the State University of Jakarta. The results of this development research were carried out product feasibility testing by experts, namely media experts obtained a percentage achievement of 87.5% with a very feasible interpretation and material experts obtained a percentage achievement of 93.8% with a very feasible interpretation. The results of the feasibility test by experts show that the 360° video microlearning developed is very feasible to be tested on students. The final product of this research is a 360° video as a medium in accordance with the predetermined learning design. This product is published through the YouTube platform to be easily accessed by students.